Recognition of power: The agency of Kurdish women in their everyday practices - Belçim Galip, Özlem (The European journal of women's studies, 2022)
Anthropological work on Kurdish women has hitherto adopted western stereotypes of power, representing it as non-existent, as women being deprived of agency in everyday practices, or totally politicized. In order to challenge prescriptive gender stereotypes, moving beyond objectification to subjectivity and offering a more complex analysis of gender relations, this study examines the position of women within their family and wider social structures in Şırnak in Turkish Kurdistan based on a sample of local women who are not employed in paid work, and their children. The implications of the results are discussed in order to enable understanding of the social structures that make it possible for women in Şırnak to exercise informal decision-making authority or to be part of the social power structures as subjects, highlighting their importance in household management and showing that ‘power’ does not necessarily equate straightforwardly with western understandings.